2022
DOI: 10.3233/jifs-219245
|View full text |Cite
|
Sign up to set email alerts
|

A new and efficient algorithm to look for periodic patterns on spatio-temporal databases

Abstract: Big Data is a generic term that involves the storing and processing of a large amount of data. This large amount of data has been promoted by technologies such as mobile applications, Internet of Things (IoT), and Geographic Information Systems (GIS). An example of GIS is a Spatio-Temporal Database (STDB). A complex problem to address in terms of processing time is pattern searching on STDB. Nowadays, high information processing capacity is available everywhere. Nevertheless, the pattern searching problem on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…Thus, we have conducted a comprehensive comparison of these algorithms over two STDBs-first, a synthetic one, then a real one. As part of our experiments, we have also included the Minus-F1 algorithm [13], which has been proven to achieve good results, and a new probabilistic version of it, which we have developed.…”
Section: Problem Definitionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, we have conducted a comprehensive comparison of these algorithms over two STDBs-first, a synthetic one, then a real one. As part of our experiments, we have also included the Minus-F1 algorithm [13], which has been proven to achieve good results, and a new probabilistic version of it, which we have developed.…”
Section: Problem Definitionmentioning
confidence: 99%
“…An efficient probabilistic algorithm: Although recent developments have produced several off-the-shelf libraries for pattern mining-for instance, apyori [14] is a library that implements the Apriori algorithm in Python-our experiments have confirmed that the performance of the most well-known algorithms is not ideal for STDBs. Thus, we have developed a new, probabilistic version of the Minus-F1 algorithm [13], which we refer to as F1/FP. This new algorithm allows for periodic pattern discovery in STDBs.…”
Section: Problem Definitionmentioning
confidence: 99%
See 3 more Smart Citations